Stability of the Malvinas Current - Beron Vera, F. J. (2020)
Deterministic and probabilistic tools from nonlinear dynamics are used to assess enduring near-surface Lagrangian aspects of the Malvinas Current. The deterministic tools are applied to a multiyear record of velocities derived from satellite altimetry data, revealing a resilient cross- stream transport barrier. This is composed of shearless-parabolic Lagrangian coherent structures (LCSs), which, extracted over sliding time windows along the multiyear altimetry-derived velocity record, lie in near-coincidental position. The probabilistic tools are applied on a large collection of historical satellite-tracked drifter trajectories, revealing weakly communicating flow regions as basins of attraction for long-time asymptotic almost-invariant sets on either side of the altimetry-derived barrier. Shearless-parabolic LCSs are detected for the first time from altimetry data, and their significance is supported on satellite-derived ocean color data, which reveal shapes that quite closely resemble the peculiar V shapes, dubbed ?chevrons,? that have recently confirmed the presence of similar LCSs in the atmosphere of Jupiter. Finally, using available in situ velocity and hydrographic data, sufficient and necessary conditions for nonlinear symmetric stability are found to be satisfied, suggesting a duality between Lagrangian and Eulerian stability for the Malvinas Current.